Analysis of the Effects of Hessian Fly (Mayetiola destructor) Parasitism on Resistant and Susceptible of Wheat Protein Synthesis - Fleming, Zachary; Motolai, Gergely; Chen, Ming (My University, 2017)
Hessian flys have caused a large amount of damage to Kansas winter wheat for over 130 years.(R. Je_ Whitworth et. al. 2009). Once wheat is parasitized the larva move from the leaves to the collar of the wheat stock where feeding occurs (Dr. Ming Chen 2017). The feeding of the larva involves the injection of saliva. This saliva is used to fundamentally change the genetics of the wheat to benefit the larva. When infected the wheat increases sugar production to feed the larva. Not only is the function of the wheat changed but also its form. The saliva also causes malformed cell growth with perforated cell membranes. This allows for easier transfers of sugars to the feeding larva (Dr. Ming Chen 2017). The end effect of the parasitism is the weakening and death of the wheat plant before the production of wheat grain can occur. (Whitworth et. al. 2009)